High-Risk HPVs and Human Carcinomas in the Syrian Population - Al Moustafa, Ala-Eddin; Ghabreau, Lina; Akil, Nizar; Rastam, Samer; Alachkar, Amal; Yasmeen, Amber (Frontiers in Oncology, 2014)
Human papillomavirus (HPV) infection is the most common sexually transmitted infection; persistent infection with high-risk types of HPV present a major risk factor for the initiation and progression of a variety of human carcinomas including cervical, colorectal, head and neck as well as breast carcinomas. A huge number of studies investigated and reported the incidence of high-risk HPVs in these cancers worldwide particularly in the developed countries; therefore, two HPV prophylactic vaccines against the two most frequent high-risk HPV types (16 and 18) have been developed and used worldwide. However, there are very limited studies about the prevalence of HPVs in the developing countries especially in Africa and some states of the Middle East (ME). In this mini review, we outline the presence of high-risk HPVs in human cervical, colorectal, head and neck as well as breast cancers in the Syrian population, which was recently explored for the first time by a Canadian/Syrian group.